Essence of the dissension in Religion: A Research Analysis in the light of Tafsīr Rūḥ al Ma’ānī - Raheem Uddin; Badshah Rehman (Journal of Islamic and Religious Studies, 2018)
The word "Ikhthilaf" refers to such an approach and way of conversation in which one scholar disagrees with another scholar. Islam being a perfect religion bars its followers from developing mutual conflicts. Islam has clearly stated that Muslim Ummah should not have differences on the basis of opinions in vivid injunctions. Such dissension has been placed nowhere in Islam. Disputes may only arise in case of secondary and vague injunctions. In such situations, each jurist considers himself as right. Such divergence, in the secondary issues based on argumentation and within the ambit of Qur’ān and Ḥadith, is not contemptible one but is the source of blessings due to the depth of knowledge of the jurists. Because of such conflicting opinions, jurisprudence and religious injunctions have the power of adaptability in accordance with the demands of the changing times. In the matters of jurisprudence, establishing consensus on the basis of argumentation must not lead to sectarianism, prejudice and hatred. True jurists have tried their level best to protect Muslim Ummah from sectarian disputes. Among such jurists we have Allama Alusī, the author of Tafsīr Rūḥ al Ma’ānī, as one big contributor. Tafsīr Rūḥ al Ma’ānī is the solid proof of his authentic and deep knowledge. It has a combination of reported sayings and exegesis of consents.